Penerapan Metode Time Out Dalam Memodifikasi Perilaku Manipulative Tantrum Pada Anak Usia 4-5 Tahun Di Desa Mirring Kabupaten Polewali Mandar (Studi Kasus) - suridha, Suridha; Asqia, Nurul; Ashari, Novita; aulia, Fitriani sulva (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
In early childhood, various kinds of behavior problems are sometimes difficult to overcome and require the right method to deal with this behavior. One of the child's behavior problems is manivulative tantrum behavior. Where this behavior appears when the child's desires are not fulfilled, and one of the behaviors shown is rebelling. The method that can be applied to modify this behavior is the time-out method. This study aims to determine the effect of applying the time-out method in modifying manipulative tantrum behavior in children aged 4-6 years. This study uses qualitative research methods, with a case study type. The subjects in this study were 5 year old children who experienced tantrum manipulative behavior. The data collection techniques used in this study were observation and interviews. The results showed that by using the time out method in dealing with tantrum manipulative behavior in children, the application of this method was effective for children who experienced this negative behavior.